Notification for Shared Annotation of Digital Documents - Brush, A.J.; Bargeron, David; Gupta, Anoop; Grudin, Jonathan (2001)
Notification and shared annotation go hand-in-hand. It is widely recognized that notification of activity in a shared document annotation system helps support awareness and improve asynchronous collaboration. But few studies have examined user needs, and there has been little exploration of design tradeoffs. We examined the large-scale use of notifications in a commercial system, and found it lacking. We designed and deployed enhancements to the system, and then conducted a field study to gauge their effect. We found that providing more information in notification messages, supporting multiple communication channels through which notifications could be received, and allowing customization of notification messages were particularly important. Overall awareness of annotation activity on specs increased with our enhancements.